Moderating effect of self-regulation on the relationship between adversity quotient and family social support on academic procrastination in thesis completion - Diya Rofika Rahmawati; Dewi Kusuma Wardani; Leny Noviani; Riyan Yuliyanto (Psikohumaniora: Jurnal Penelitian Psikologi)
Final assignments are part of the strategy to train students' skills, but they often cause feelings of stress and lead to students choosing to postpone them. This research aims to determine how the influence of Adversity Quotient (AQ) and Family Social Support (FSS) on academic procrastination attitudes in completing a bachelor theses is moderated by Self-regulated Learning (SRL). The study was conducted in two state universities in Indonesia on students who had not completed their theses. Data collection was made through a survey, with online questionnaires based on Likert Scales using Google Forms. The instruments used were the Adversity Quotient (AQ) Scale, the Family Social Support (FS) Scale, the Self-regulated Learning (SRL) Scale, and the Academic Procrastination in Completing Bachelor Theses (APCBT) Scale. Data analysis was conducted using moderated regression analysis. The research results show an influence of the adversity quotient ( t = -2.165, p < .031) and family social support (t = 5.512, p < .000) on academic procrastination in completing theses. Self-regulated learning is demonstrated to moderate the relationship between adversity quotient and academic procrastination in completing theses (t = -2.126, p < .035), while self-regulated learning moderates the relationship between family social support and academic procrastination in completing theses (t = -4.831, p < .000). The empirical implication of this study is that during the theses preparation process, final-year students may face psychological challenges, so it is not uncommon for them to postpone work by introducing self-regulated learning roles, difficulty intelligence, and family social support can help students in suppressing the problem of academic procrastination in theses completion.